SITUATION OF LIVESTOCK MARKETING CENTERS IN TUNGURAHUA - ECUADOR DURING THE COVID-19 PANDEMIC - Curay, Carlos (2023)
Covid-19 destabilized the social, political, economic systems and affected the commercialization of cattle, sheep, goats, pigs, guinea pigs, rabbits and poultry, reducing the establishments dedicated to the sale of these species. 184 surveys were applied to livestock producers who marketed in Tungurahua where eight establishments authorized by Agrocalidad were identified. In order to describe the livestock marketing centers, a methodology and descriptive statistics were, analyzed using the IBM SPSS STATISTICS version 22 software, obtaining that the average age of the producers was 37 years, 54.7% are male and their place of origin of the same is greater for Ambato with 17.5%. It is determined that 81.3% claim to know the livestock marketing centers in the province; while 100% know which market to go to sell their animals. The Agricultural Marketing Center (CEMEAG) of the Ambato canton is considered the second most important fair at the national level, for this reason, 32.9% visit it frequently. The species with the greatest commercial importance are cattle (42.4%) and pigs (19.3%). 71.2% consider that the effect of the pandemic on the economy and the commercialization of animals was positive since they worked without intermediaries.